Plant-derived Ren's oligopeptide has antiviral effects on influenza virus and SARS-CoV-2 - Yu, Chengzhi; Huang, Yayu; Ren, Xin; Sun, Leqiang (Frontiers in Veterinary Science, 2023)
Influenza virus and SARS-CoV-2 virus are two important viruses that cause respiratory tract diseases. The high-frequency mutation of the two types of viruses leads to failure of the durable immune protection of vaccines, meanwhile it also poses continuous challenges to the development of antiviral drugs. Traditional Chinese medicine contains large number of biologically active compounds, and some of them contain broad-spectrum antiviral ingredients. In this study, we extracted antiviral active ingredients from medicinal and edible plants by biotransformation and enzymatic hydrolysis as a drug, and we named this drug Ren's oligopeptide. Further, we analyzed the antiviral activity of this drug and found that Ren's oligopeptide could inhibit the replication of influenza virus and SARS-CoV-2 virus with high anti-virus activities. In vitro experiments showed that the antiviral activity of the Ren's oligopeptide mainly targets the replication process after virus enters the cell. Therefore, Ren's oligopeptide is a promising drug against influenza and COVID-19.